Strategi Guru Dalam Meningkatkan Kemampuan Berpikir Peserta Didik di Era Teknologi - Dini Silvina; Shalshabila Shalshabila; Gusmaneli Gusmaneli (IHSANIKA : Jurnal Pendidikan Agama Islam, 2025)
The rapid development of information and communication technology has changed the paradigm of learning in the current digital era. Teachers are required to be able to integrate technology into the learning process in order to improve students' critical and creative thinking skills. Critical thinking skills are the main skills that students must have in order to be able to sort, analyze, and evaluate information appropriately amidst the rapid flow of digital information. Therefore, the learning strategies implemented by teachers must be able to facilitate the development of students' thinking skills by utilizing various digital media and technologies effectively. This study aims to identify and analyze teacher strategies in improving students' critical thinking skills in the technological era, especially through digital literacy. The strategies implemented include learning planning that integrates digital media such as laptops, projectors, internet networks, and online learning platforms (e-learning). The implementation of learning uses problem-based learning methods and collaborative learning that encourage students to be active in discussions, case analysis, and problem solving together. Learning evaluation is also carried out interactively by utilizing technology to measure students' critical thinking skills more accurately and in real-time. In addition, teachers provide motivation and rewards as an effort to increase students' self-confidence in critical thinking. The use of audio-visual media, videos, and interactive modules is also an important strategy to attract students' interest in learning and link learning materials to real-life contexts. Teachers act as facilitators who guide students in mastering information, analyzing various points of view, and developing creative solutions to problems faced. Digital literacy education is also taught to equip students with the ability to sort valid information and avoid the spread of false information. By implementing these strategies, students' critical thinking skills can increase significantly, so that they are better prepared to face the challenges of learning in the digital era and are able to actively participate in the information society. This study emphasizes the importance of the role of teachers in developing critical thinking skills through the use of technology and digital literacy as part of the 21st century competencies that students must have.